Measuring Individual Risk Attitudes in the Lab: Task or Ask? An Empirical Comparison - Philipp C. Wichardt; Jan-Erik Lönnqvist; Markku Verkasalo; Gari Walkowitz (Verein für Socialpolitik, 2010)
This paper compares two prominent empirical measures of individual risk attitudes - the Holt and Laury (2002) lottery-choice task and the multi-item questionnaire advocated by Dohmen, Falk, Huffman, Schupp, Sunde and Wagner (forthcoming) - with respect to (a) their correlation with actual risk-taking behaviour in the lab - here the amount sent in a trust game, and (b) their within-subject stability over time (one year). As it turns out, only the questionnaire measure is correlated with actual risk-taking behaviour (both studies) and with the Big Five personality measure (gathered prior to study 1); and the measures themselves are uncorrelated (both studies). Most importantly, however, both individual risk-taking behaviour and the questionnaire measure exhibit a significant high test-retest stability (r = 0:70 and r = 0:79, resp.), while virtually no such stability is present in the lottery-choice task. Thus, the results suggest that the questionnaire measure is more reliable in eliciting individual risk attitudes than the lottery-choice task. Moreover, with respect to trust, the data further support the conjecture that trusting behaviour indeed has a component which itself is a stable individual characteristic (Glaeser, Laibson, Scheinkman and Soutter, 2000).
Keywords: D81; C91; Z10; 330; Risk Attitudes; Trust; Personality; Lab Experiments